Analysis of Human Resource Management at Nasari Syariah Savings and Loan Cooperative, Lhokseumawe - Vivin Mahenrato; Muhammad Fajar Hidayat; Frengki Putra Ramansyah; Akmal (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze human resource management (HR) in the Nasari Syariah Savings and Loan Cooperative (KSP) Lhokseumawe with a focus on organizational structure, work motivation, HR training and development, and the main challenges faced. Through a field survey approach and interviews with cooperative administrators and members, it was found that the cooperative has a fairly systematic organizational structure with defined roles. In increasing work motivation, the cooperative implements a reward system that has succeeded in improving member performance. In addition, routine training and development are provided to improve the quality of sharia-based services. However, the cooperative still faces various challenges such as limited technology, difficulties in recruiting young workers, and internal conflict management. The results of this study indicate that a sharia-based strategy is an effective approach in managing cooperative HR.